Ефективність діяльності суб’єктів ринку автосервісу та автомобілів в Україні в умовах воєнного стану - Майстро, Руслана Григорівна; Білецький, Сергій Михайлович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Стаття висвітлює виклики, з якими стикається ринок автосервісу та автомобільної торгівлі в Україні в умовах воєнного стану, підкреслюючи критичну роль економічної ефективності підприємств у забезпеченні їх стійкості. В умовах скорочення купівельної спроможності населення, зростання цін на запчастини та логістичних труднощів, ефективність стає ключовим фактором виживання підприємств. Основна увага приділяється адаптаційним стратегіям, які впроваджують компанії для мінімізації ризиків та оптимізації операційної діяльності. Окремий акцент зроблено на інноваційних підходах підприємств Харківського регіону, таких як "Альфа Діамант" і "Харків-Авто", що демонструють успішні приклади реагування на виклики кризи. The article examines methods of reasoning and making business decisions. It was determined that in the conditions of war the risks increase, so it is necessary to approach the formation of business decisions more thoroughly. The decision-making process involves identifying the problem, choosing options, and evaluating the effectiveness of the solution. It is noted that the adaptability of business to risks and changes opens perspectives in many directions and creates a strategic and competitive advantage, enables businesses to become market leaders. It was determined that in order to achieve the desired state of business in critical conditions, it is necessary to clearly follow the algorithm for building a decision-making model, which will take into account the full validity of the adopted business decision based on the identified problems, use various methods of making business decisions depending on the situation, and also build priority values when justifying business decisions and implementing them in the event of a threat to the enterprise andthe life and health of people.
Efficiency of activities of vehicle service and car market in Ukraine under the conditions of marital state
Keywords: економічна ефективність; воєнний стан; автосервіс; автомобільна торгівля; стійкість; конкурентоспроможність; economic efficiency; automobile trade; competitiveness; martial law